Paralysed with Fear - Williams, Gareth. author. aut Link
XIX, 354 p.
Keywords: The story of mankind's struggle against polio is compelling, exciting and full of twists and pardoxes. One of the grand challenges of modern medicine, it was a battleground between good and bad science. Gareth Williams takes an original view of the journey to understanding and defeating polio.